(untitled) (Bulletin KNOB, 1998)
This article concentrates on the oldest stone churches in the former county of Holland. The oldest examples to have survived were built of tuff, an expensive material, that was imported from the Eifel-region. It is argued that apart from the count himself, the local nobility acted as patrons of many of these churches, and that these served to show off their status and prestige, and at the same time functioned as mausolea for themselves and their descendants, as is suggested by the existence of imported, and therefore expensive, sarcophagi and sarcophagus-lids of red sandstone in many of the tuff churches. Other tuff churches were built in the border areas and in regions that had recently been brought under the control of the count of Holland, i.e. West-Friesland. The churches in this latter region served as a stabilizing factor in an area that had been disrupted by warfare for many years, as tokens of the newly-established peace, to commemorate the mutual dead (interestingly, there are very large numbers of sarcophagus-lids of red sandstone in this region) and in order to control the inhabitants of the area.